Requirement Volatility, Standardization and Knowledge Integration in Software Projects: An Empirical Analysis on Outsourced IS Development Projects - Rajesri Govindaraju; Angra Bramagara; Leksananto Gondodiwiryo; Tota Simatupang (Journal of ICT Research and Applications, 2015)
Information systems development (ISD) projects are highly complex, with different groups of people having  to collaborate and exchange their knowledge. Considering the intensity of knowledge exchange that takes place in outsourced ISD projects, in this study a conceptual model was developed, aiming to examine the influence of four antecedents, i.e. standardization, requirement volatility, internal integration, and external integration, on two dependent variables, i.e. process performance and product performance. Data  were collected from 46 software companies in four big cities in Indonesia. The collected data were examined to verify the proposed theoretical model using the partial least square structural equation modeling (PLS-SEM) technique. The results show that process performance is significantly influenced by internal integration and standardization, while product performance is  significantly influenced by external integration and  requirement volatility. This study contributes  to a better understanding of how knowledge integration can be managed in outsourced ISD projects in view of increasing their success.